Pelestarian Tari Babukung Sebagai Media Edukasi Seni Budaya Di Kalimantan Tengah - Annisa Awliya; Wendy Martanto; Tasya Erya Mareta; Ananda Erliana; Haulani Abigael Pai (Tambuleng, 2025)
Babukung Dance is one of the traditional dances from the Dayak Tomun tribe in Central Kalimantan, precisely in Lamandau Regency. This dance is usually performed in death ceremonies as a form of tribute to the spirits of ancestors. However, currently the existence of Babukung dance is beginning to be threatened due to the influence of foreign cultures and the lack of the younger generation to learn and preserve it. This research aims to see how Babukung dance can be used as a learning medium or cultural education in schools and the community. The method used is descriptive qualitative research, namely by observing (observation), interviewing traditional figures, teachers, and local artists, as well as reading various literature sources. The results show that Babukung dance is very useful for introducing local culture to children and teenagers. Culture can only survive if it continues to be passed down to the next generation. Therefore, Babukung dance needs to be taught in schools, trained in art studios, and performed in cultural events. That way, children will know and be proud of their own local culture.